Self-Made Vocabulary Cards and Differentiated Assessments to Improve an Autistic Learner’s English Vocabulary Mastery - Subekti, Adaninggar Septi (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2020)
As autistic learners exhibit different behaviours from their peers, they need differentiated instruction in learning. Hence, to provide equal learning opportunities for a learner with autism based mainly on the principle of modification changing the expected standard performance of the autistic learner, this study employed differentiated instruction consisting of two treatments in Vocabulary Building class. They were the use of self-made vocabulary cards as the basic learning materials and differentiated assessments consisting of quizzes, mid-semester assessment, and final assessment providing opportunities for recycle and repetition beneficial for vocabulary retention and learning in general. The findings indicated that the autistic learner showed satisfactory results on his mastery of bilingual (Indonesian to English) word equivalence written in the vocabulary cards and thus obtained satisfactory scores in the corresponding assessments. He, however, still struggled in using the words he studied in grammatical and comprehensible English sentences. With teacher’s verbal step-by-step prompts, however, he could formulate simple grammatical sentences. Based on the results, implications, limitations and suggested directions of future studies are presented.